Blefaroespasmo. Distonía oromandibular - Micheli, F.; Fernández-Pardal, M.; Pikielny, R.; Gatto, M.; Giannaula, R.; Casas, I.; Scorticati, M.; Zurru, C.; Diaz, S. (Revista de Neuro-Psiquiatría, 2013)
.